IMPLEMENTASI KEBIJAKAN DISIPLIN PEGAWAI NEGERI SIPIL DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SULAWESI TENGAH - Yunita Laponte; Nurhannis; Nur Alamsyah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The purpose in this research is to analyze the implementation of the Civil Servant Discipline policy at the Secretariat of the Regional People's Representative Council of Central Sulawesi Province. The selection of informants used purposive sampling, namely by selecting 5 informants. Data was collected through observation, interviews and documentation techniques. In this research, researchers used the analytical approach technique of Milles Hubermen and Saldana. The research results are transmission, clarity, consistency, so it can be described that communication has not gone well in supporting the implementation of policies regarding civil servant discipline at the DPRD. The disposition has not worked as it should because the character of the policy implementer, in this case the leadership, is one of the keys to success in improving civil servant discipline at the Central Sulawesi Provincial DPRD Secretariat. The bureaucratic structure implemented is working quite well because there are SOPs, the most important of which is firmness from the leadership at the Central Sulawesi Provincial DPRD Secretariat.